PENGARUH GREEN MARKETING, BRAND AWARENESS, DAN PERCEIVED VALUE TERHADAP PURCHASE INTENTION KONSUMEN UNILEVER DI KUDUS - Suparwi, Suparwi; Jannah, Laukhatul (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
The purpose of this study was to determine the effect of green marketing, brand awareness, perceived value on the purchase intention of Unilever consumers in Kudus. The approach used in this research is a quantitative approach. The population in the population in this study were all Unilever consumers in Kudus. The sampling technique used simple random sampling technique. Data collection was carried out by distributing questionnaires as a research instrument to 96 respondents. The data analysis technique used multiple linear regression analysis with various statistical tests using the SPSS version 23 application. The statistical tests carried out included validity tests, reliability tests, classical assumption tests, and hypothesis testing. The results of the study show that Green Marketing, Brand Awareness, Perceived Value have a positive and significant effect on Purchase Intention